The Mixed Nature of Incentives for Community Health Workers: Lessons from a Qualitative Study in Two Districts in India - Sarin, Enisha; Lunsford, Sarah Smith; Sooden, Ankur; Rai, Sanjay; Livesley, Nigel (Frontiers in Public Health, 2016)
Incentives play an important role in motivating community health workers (CHWs). In India, accredited social health activists (ASHAs) are female CHWs who provide a range of services, including those specific to reproductive, maternal, neonatal, child, and adolescent health. Qualitative interviews were conducted with 49 ASHAs and one of their family members (husband, mother-in-law, sister-in-law, or son) from Gurdarspur and Mewat districts to explore the role of family, community, and health system in supporting ASHAs in their work. Thematic analysis revealed that incentives were both empowering and a source of distress for ASHAs and their families. Earning income and contributing to the household’s financial wellbeing inspired a sense of financial independence and self-confidence for ASHAs, especially with respect to relations with their husbands and parents-in-law. In spite of the empowering effects of the incentives, they were a cause of distress. Low incentive rates relative to the level of effort required to complete ASHA responsibilities, compounded by irregular and incomplete payment, put pressure on families. ASHAs dedicated much of their time and own resources to perform their duties, drawing them away from their household responsibilities. Communication around incentives from supervisors may have led ASHAs to prioritize and promote those services that yielded higher incentives, as opposed to focusing on the most appropriate services for the client. ASHAs and their families maintained hope that their positions would eventually bring in a regular salary, which contributed to retention of ASHAs. Incentives, therefore, are both motivating and inspiring as well as a cause dissatisfaction among ASHAs and their families. Recommendations include revising the incentive scheme to be responsive to the time and effort required to complete tasks and the out-of-pocket costs incurred while working as an ASHA; improve communication to ASHAs on incentives and responsibilities; and ensure timely and complete payment of incentives to ASHAs. The findings from this study contribute to the existing literature on incentivized CHW programs and help throw added light on the role incentives play in family dynamics which affects performance of CHW.